Religiusitas dan Perilaku Kecurangan Akademik Mahasiswa di Masa Pandemi Covid-19 - Diana Br Sihite; Evi Maria (AFRE (Accounting and Financial Review), 2022)
The purpose of this research is to examine the effect of religiosity and academic cheating of accounting students on online learning during the Covid-19 pandemic. This research was conducted on accounting students at Satya Wacana Christian University, with a total sample of 150 students. Data was collected from questionnaires distributed via email and other social media using google forms. Data were analyzed using linear regression analysis. The results of the research found that religiosity had a negative effect on the academic cheating behavior of accounting students during the Covid-19 pandemic. This means, the higher the level of religiosity of accounting students, the lower the level of academic cheating committed by accounting students during online learning during the pandemic, and vice versa. Therefore, the Accounting Study Program needs to increase the religiosity of its students, so that academic fraud can be reduced and the program can produce accountants and auditors who are honest and with integrity.DOI: https://doi.org/10.26905/afr.v5i3.8049